Dynamic Spectral Analysis Problems - Краковский, В. Я. (Problems of Informatization and Control, 2005)
Dynamic spectral analysis execution possibilities are analyzed. At different correlations between analysis sliding window sizes and displacements of the following windows with respect to preceding ones, spectrum computation type choosing advisability estimate is given